UPAYA INTERNALISASI KARAKTER RELIGIUS PESERTA DIDIK MELALUI PROGRAM FULL DAY SCHOOL - Yanti, Yuni Widya; Choiri, Moh. Miftachul (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
Along with the development of digitalization, the character of elementary school-age children is experiencing many problems. Among these problems is related to the development of religious character. Problems related to religious character include; indifferent to the practice of prayer, preferring foreign cultures, attaches more importance to games than learning to read the Quran, prefers to bully rather than appreciate. To foster the development of children's religious character, there needs to be an internalization of pesantren values, these values are the five souls of modern boarding schools consisting of; The soul of simplicity, the soul of simplicity, the soul of independence, the soul of Islamic ukhuwah and the soul of freedom. This study seeks to describe the process of internalizing the value of the K.H. Imam Zarkasyi Islamic boarding school at MI Al-Hikmah Ponorogo. The approach of this research is qualitative, the type of case study results show that the internalization of values to the Kyai Haji Imam Zarkasi Islamic boarding school at MI Al-Hikmah Ponorogo has a significant impact on the development of students' religious character. Internalization of religious character through a full-day school program with the strategy used, namely planning concepts and materials taught. The obstacles to the internalization of religious character based on the values of K.H. Imam Zarkasyi's pesantren at MI Al-Hikmah Ponorogo are sourced from internal and external factors.